The protein and volatile components of trail mucus in the Common Garden Snail, Cornu aspersum. - Kaylene R Ballard; Anne H Klein; Richard A Hayes; Tianfang Wang; Scott F Cummins (PLoS ONE)
The Common or Brown Garden Snail, Cornu aspersum, is an invasive land snail that has successfully colonized a diverse range of global environments. Like other invasive land snails, it is a significant pest of a variety of agricultural crops, including citrus, grapes and canola. Cornu aspersum secretes a mucus trail when mobile that facilitates locomotion. The involvement of the trail in conspecific chemical communication has also been postulated. Our study found that anterior tentacle contact with conspecific mucus elicited a significant increase in heart rate from 46.9 to 51 beats per minute. In order to gain a better understanding of the constituents of the trail mucus and the role it may play in snail communication, the protein and volatile components of mucus trails were investigated. Using two different protein extraction methods, mass spectrometry analysis yielded 175 different proteins, 29 of which had no significant similarity to any entries in the non-redundant protein sequence database. Of the mucus proteins, 22 contain features consistent with secreted proteins, including a perlucin-like protein. The eight most abundant volatiles detected using gas chromatography were recorded (including propanoic acid and limonene) and their potential role as putative pheromones are discussed. In summary, this study has provided an avenue for further research pertaining to the role of trail mucus in snail communication and provides a useful repository for land snail trail mucus components. This may be utilized for further research regarding snail attraction and dispersal, which may be applied in the fields of agriculture, ecology and human health.